Software switch for DC motor controller / Mohd Sufian Ibrahim - Ibrahim, Mohd Sufian (1996)
A software switch is realized to achieve motion control using DC motors. The controller, utihlizing inierrupt driven software switch scheme, is capable of implementing several control strategies such as the continuously variable or discrete pulse width control and phase control of pulse width modulation (PWM) converters. The control methodology is adaptable to diverse industrial application settings. Switching scheme is implemented using C+- language environment. Implementation in software, provides the capability of executing complex control schemes and supervisory functions which are easy to implement, update and adapt to different applications without much overhead.